Assessing the usage risk of the emerging Green Chemical potassium ferrate in aquaculture environments in China: A probabilistic statistical approach. (15th November 2022) - Cao, Guoqing; Qiu, Liping; Yang, Guang; Chen, Xi; Wang, Xinchi; Gui, Yuan; Fan, Limin; Meng, Shunlong; Song, Chao
Abstract: In recent years, the food safety of aquatic products has become an increasing concern worldwide. Using conventional disinfectants and antibiotic drugs in the aquaculture industry may cause a decline in product quality. Compared to traditional water quality improvers, the green, emerging chemical potassium ferrate plays a significant role in improving aquaculture environments and the quality of aquatic products, yet the usage of potassium ferrate is blind, and the ecological risk is unclear due to the lack of knowledge of its scientific use. In this study, a probabilistic statistical model to assess the risk of potassium ferrate use is demonstrated for the first time. The results show that the annual output of potassium ferrate is about 900 t in China, with the usage dose ranging from 10 to 120 μg/L. The oxidation reduction potential (ORP) of potassium ferrate will return to a stable state within 72 h of the water quality treatment process, implying that there is no longer oxidative toxicity after 72 h. Acute toxicity tests have shown that potassium ferrate is of low toxicity to typical aquaculture organisms (cultured fish and crustaceans) with 72 h LC50 values in the range of 95–609 mg/L, while it is highly toxic to the planktons tested with values of 1.0 and 4.3 mg/L. The joint probability curve analysis indicates that 30 μg/L (low daily usage dose), 60 μg/L (median daily usage dose), and 120 μg/L (high daily usage dose) of potassium ferrate can affect 1.06%, 2.15%, and 4.04% of aquatic species (aquaculture organisms and planktons), with a risk probability of 54.47%, 19.34%, 3.35%, while the risk to aquaculture organisms is 0. The research shows that the current concentrations of potassium ferrate used are of very low risk to aquaculture organisms, while also inhibiting planktons to improve water quality. This study plays an important role in guiding the safe use of potassium ferrate and improving water quality. Policymakers and scientists can draw support from these results and approaches when evaluating the use of potassium ferrate. Graphical abstract: Image 1 Highlights: The usage risk of potassium ferrate in aquaculture environments was firstly quantitatively assessed. Compared with plankton productivity, potassium ferrate showed lower toxicity to cultured fish and crustaceans. The current usage of potassium ferrate was of very low risk for aquaculture organisms.